Brain Machine Interface: A Review of Current Technologies and Future Directions - Rahul Singh; Sachin Sharma (International Journal of Biomedical Innovations and Engineering, 2023)
Brain Machine Interface (BMI) is a rapidly growing field that aims to establish direct communication between the brain and an external device. This technology has the potential to restore lost motor and sensory functions in people with neurological disorders or injuries. A brain-computer interface (BCI) is a technology that converts signals from the brain into instructions for computers or other gadgets. This innovation allows individuals to engage with their surroundings solely through their brain's actions, eliminating the necessity for peripheral nerves and muscles. The development of devices that enable impaired people to communicate with others, operate prosthetic limbs, or regulate their surroundings is the main objective of BCI research. Multimedia communication is a promising application area for brain-computer interfaces (BCIs). Currently, many aspects of BCI systems are being investigated to develop systems for assistive technology and multimedia communication. These research areas include assessing invasive and non-invasive technologies to measure brain activity, evaluating control signals (patterns of brain activity that can be used for communication), developing algorithms for translating brain signals into computer instructions, and creating new BCI applications. The aim of this paper is to provide an overview of the current state of BMI technologies, as well as to explore their potential applications and future directions.
Keywords: BMI; Brain Machine Interface; Multimedia communication; invasive; non-invasive